Propolis as an Adjuvant for Colon Cancer Chemotherapy: Exploring its Potential on Apoptosis, Cell Cycle, and PI3K Expression - Suryani Eka Mustika; Aznan Lelo; Iqbal Pahlevi Nasution; Poppy Anjelisa Hasibuan; Putri Chairani Eyanoer; Muhammad Ichwan; Rustam Effendi; Mustofa (مجلة بغداد للعلوم, 2024)
Propolis as co-chemotherapy is believed to reduce the severity of chemotherapy's adverse effects. The combination of propolis and chemotherapy is expected to induce apoptosis, arrest the cell cycle, and downregulate the expression of Phosphatidylinositol-3 kinase (PI3K), thereby reducing the proliferation of colon cancer cells (WiDr). The WiDr cells were obtained from the parasitology lab of the medical school at Universitas Gadjah Mada in Yogyakarta, Indonesia. Propolis is collected by beekeepers in Kabanjahe, North Sumatra. Cytotoxicity of the WiDr cell line was tested using the Microculture Tetrazolium Technique (MTT) assay. The therapy group was divided into seven subgroups. The experiment involved treating WiDr cells with different substances: K for control (normal), F for 20 µg/mL 5-FU, O for 5 µg/mL oxaliplatin, P for 7.5 µg/mL propolis, PF for a combination of 7.5 µg/mL propolis and 20 µg/mL 5-FU, PO for a combination of 7.5 µg/mL propolis and 5 µg/mL oxaliplatin, and FO for a combination of 5 µg/mL oxaliplatin and 20 µg/mL 5-fu. Flow cytometry was employed to investigate apoptosis, cell cycle, and PI3K profiles. The combination of propolis with either 5-FU or oxaliplatin enhanced both early and late apoptosis. Additionally, inhibition of the cell cycle at the G0-G1 and S phases was observed when propolis was combined with either 5-FU or oxaliplatin. PI3K expression was inhibited by propolis in combination with 5-fu or oxaliplatin. Propolis, used as co-chemotherapy, displayed anticancer efficacy through inducing apoptosis, boosting cell cycle, and suppressing PI3K expression.